Odpowiedzi

Najlepsza Odpowiedź!
  • Yawe
  • Początkujący
2009-12-16T19:40:18+01:00
Y²- (y-3)²= 3
y²- (y²-6y+9)= 3
y²-y²+6y-9=3
6y=12
y=2

(4x-y)² -2 (2x+2)(4x+2) Podstawiam x=3 i y=-2
(4*3-(-2))²-2(2*3+2)(4*3+2)=
=(12+2)²-2*8*14=
=14²-16*14=
=-28

Jego pole (P) wyniesie a(a+b) jeśli podane jest tam pole i trzeba ułożyć równanie to dla pola np. 2 będzie równanie 2=a(a+b)
2009-12-16T19:45:48+01:00
Y² - (y-3)² = 3
y² - (y² - 6y + 9) = 3
y² - y² +6y - 9 = 3
6y - 9 = 3
6y = 3 + 9
6y = 12 /:6
y = 2

2) (4*3 - (-2))² -2 (2*3 + 2)(4*3 + 2)=
= (12+2)² - 2 (6+2)(12+2)=
=14² - 2*8*14=
= 196 - 224= -28

3)
p = a*(a+b)
p = a² + ab